Economic model predictive control of boiler-turbine system. (June 2018) - Liu, Xiangjie; Cui, Jinghan
Highlights: An economic model predictive control with input constraints handling is developed for boiler-turbine system. A stable Sontag controller and corresponding region are designed off-line to ensure the stability of the closed-loop system. The optimization problem of economic model predictive control is solved on-line with dynamic economic optimization mode and guaranteeing stability mode. The dynamic response and economic performance of the economic MPC under various types of commonly encountered load changes has been tested in the plant simulation. Abstract: In a modern power plant, the economy of boiler-turbine system has recently aroused too much concern, while load tracking is no longer the only significant task for control and optimization purpose. Traditionally, the economy of the boiler-turbine system has been handled in a multi-layer hierarchical architecture, which neglects the economy of the dynamic tracking process. In this paper, an economic model predictive controller is developed. It directly utilizes the economic index of boiler-turbine system as the cost function and realizes the economic optimization as well as the dynamic tracking. A stable Sontag controller and corresponding region are designed to ensure the stability of the closed-loop system. Then, the optimization problem of this economic model predictive control is solved on-line using Laguerre functions. Simulations are given to show the effectiveness of the proposed controller.